The Effect of Foliar Application with Naphthalene Acetic Acid and Potassium Nitrate on the Growth, Sex Ratio, and Productivity of Cucumbers (Cucumis sativas L.) under High Temperatures in Semi-Arid Areas - Mashael M. Alotaibi; Mohamed M. M. El Nagy; Makhdora Almuziny; Moodi S. Alsubeie; Amero A. I. Abo-Zeid; Fahad Mohammed Alzuaibr; Abdulrahman Alasmari; Bedur Faleh Albalawi; Ahmed H. M. Abd-Elwahed; Khadiga Ahmed Ismail; Mamdouh M. A. Awad-Allah (Agronomy, 2024)
High temperatures in late spring, summer, and autumn are one of the main elements limiting cucumber production. Heat stress in cucumber plants leads to significant changes in sex expression and negative effects at the physiological stage, including decreased absorption of water and nutrients, decreased photosynthetic functions, and increased respiration, which in turn affects growth and production. Therefore, it is very difficult for cucumber plants exposed to heat stress to improve their productivity, especially in arid and semi-arid regions. Cucumber plants bear a variety of flower forms, including staminate, pistillate, and hermaphrodites that occur in different arrangements. In addition, maleness is considered the main problem in cucumber production, as it significantly reduces fruit yield. Recently, the growth, flowering, and productivity of plants have been controlled with the help of growth-regulating substances, and one of these substances is naphthalene acetic acid (NAA), which is of great importance in modifying sex in cucumber and various cucurbit crops. Two experiments were conducted during 2022 and 2023 during the summer season to study the effect of foliar spraying of two levels of potassium nitrate, 500 mg/L and 1000 mg/L, and two levels of NAA, 50 mg/L and 100 mg/L, individually and together, and the comparison treatment in nine treatments on growth traits, sex ratio, fruit traits and yield of cucumber (Cucumis sativas L.) plants in three replicates in a completely randomized block design. The results indicated that applying the treatment containing 1000 mg/L KNO3 + 100 mg/L NAA led to obtaining the highest value in most vegetable growth, flowering, and production parameters, with a significant increase compared to the control and all other treatments. Followed by treatments consisting of potassium nitrate and NAA, which gave high values in the traits of sex ratio %, fruit setting %, fruit yield, and most other traits. This study showed the importance of spraying with both NAA and potassium nitrate, individually or in combination, and the high combined effect of both in the treatments that contained each of them in the vegetative growth traits and floral traits such as the number of female flowers, the sexual ratio, fruit set percentage, weight fruit, length fruit, and the fruit yield in cucumber plants grown in the summer season with high temperatures